2016
DOI: 10.3233/sw-150193
|View full text |Cite
|
Sign up to set email alerts
|

An unsupervised data-driven method to discover equivalent relations in large Linked Datasets

Abstract: Abstract. This article addresses a number of limitations of state-of-the-art methods of Ontology Alignment: 1) they primarily address concepts and entities while relations are less well-studied; 2) many build on the assumption of the 'well-formedness' of ontologies which is unnecessarily true in the domain of Linked Open Data; 3) few have looked at schema heterogeneity from a single source, which is also a common issue particularly in very large Linked Dataset created automatically from heterogeneous resources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Existing Semantic Web tools to discover equivalent relationships between EHR coded values and terms from the LOD cloud were explored for this work. However, most schema definitions are not necessarily well formed in the domain of LOD [39] and cannot be seamlessly crawled. In addition, the quality of these LOD datasets in terms of completeness, consistency, conciseness, and interlinking remains a challenge [40].…”
Section: Discussionmentioning
confidence: 99%
“…Existing Semantic Web tools to discover equivalent relationships between EHR coded values and terms from the LOD cloud were explored for this work. However, most schema definitions are not necessarily well formed in the domain of LOD [39] and cannot be seamlessly crawled. In addition, the quality of these LOD datasets in terms of completeness, consistency, conciseness, and interlinking remains a challenge [40].…”
Section: Discussionmentioning
confidence: 99%
“…Unsupervised learning usually achieves normalization from a text morphology perspective by calculating the text similarity, or by string matching vocabulary with existing knowledge base concepts. Gunaratna et al [22] and Zhang et al [23] identified synonymous attributes in Linked Open Data (LOD) [24] using overlap between triples; the latter gives an unsupervised framework for the attribute normalization. Ristad et al [25] calculated the text similarity using string edit distance to achieve attribute normalization.…”
Section: Related Workmentioning
confidence: 99%
“…Severalissueshavebeeninvestigatedin (Zhang,Gentile,Blomqvist,Augenstein,&Ciravegna, 2017),e.g.,manyoftheLODontologiesareincompleteandnoisyandarenotwell-structuredand welldefined.Thealignmentofheterogeneousrelationshipsisnotproperlyaddressedbecauseof synonymyandpolysemy,lackofstructuralinformationaboutrelations,inconsistencyinthemeaning andusageofschemata.TheinteroperabilityofLOD-basedapplicationsisalsoaffectedduetorare linksatschemalevelLODdatasets(asmostoftheresearchfocusedthedatalevellinksinLOD datasets) (Zhangetal.,2017).…”
Section: Matching Ontologiesmentioning
confidence: 99%